2020
DOI: 10.1111/jfbc.13451
|View full text |Cite
|
Sign up to set email alerts
|

Dietary monosodium glutamate altered redox status and dopamine metabolism in lobster cockroach ( Nauphoeta cinerea )

Abstract: Monosodium Glutamate (MSG), also referred to as sodium glutamate, is the known sodium salt of the amino acid; glutamate or glutamic acid. It is commonly used at home, fast food restaurant, and in the food industry because of its flavor and umami taste that increases the meaty, spicy, and acceptable flavor of food and food products, just like the taste of natural glutamate. It is the major component of stock cubes, seasonings, and spices used in soups, ramen, gravy, stews, condiments, smoked meat products, hamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
1
0
0
Order By: Relevance
“…Lipid peroxidation (LPO) is characterized as irreversible degradation of plasma membrane lipids, generating a series of degradation products such as malondialdehyde (MDA); its significant levels are detectable as species reactive to thiobarbituric acid (TBARS), a marker of oxidative stress [ 53 ]. The substance NJ20 caused a significant increase in MDA at a concentration of 1 mM ( Figure 5 ), similar to the effect observed for sodium glutamate, a potent neurotoxic agent [ 49 , 54 ]. However, NW05 caused a reduction in levels when compared to the control group, results that corroborate those of Bittencourt et al [ 55 ], who found that isolated caffeine decreased the damage induced by lipid peroxidation by 25%.…”
Section: Discussionsupporting
confidence: 76%
“…Lipid peroxidation (LPO) is characterized as irreversible degradation of plasma membrane lipids, generating a series of degradation products such as malondialdehyde (MDA); its significant levels are detectable as species reactive to thiobarbituric acid (TBARS), a marker of oxidative stress [ 53 ]. The substance NJ20 caused a significant increase in MDA at a concentration of 1 mM ( Figure 5 ), similar to the effect observed for sodium glutamate, a potent neurotoxic agent [ 49 , 54 ]. However, NW05 caused a reduction in levels when compared to the control group, results that corroborate those of Bittencourt et al [ 55 ], who found that isolated caffeine decreased the damage induced by lipid peroxidation by 25%.…”
Section: Discussionsupporting
confidence: 76%